A General Description of Hardiness among Islamic Senior High School Students at Miftahul Ulum Islamic Boarding School - Maya Nurhasanah; Muhammad Muhajirin; Agung Nugraha (Journal of Mental Health and Well-Being in Counseling, 2026)
This study aims to provide an overview of the level of hardiness among senior high school students (santri) at islamic boarding school miftahul ulum ciamis. Hardiness is understood as a personality characteristic that helps individuals remain stable and adaptive when facing pressure. The research employed a descriptive quantitative approach involving one hundred senior high school students using a saturated sampling technique. Data were collected through the fifteen-item Dispositional Resilience Scale, which assesses three dimensions of hardiness: commitment, control, and challenge. The findings indicate that most students fall into the high and moderate hardiness categories, while a smaller portion belongs to the low category. In the commitment dimension, the majority of students are classified in the moderate category, whereas in the control and challenge dimensions, more students are categorized as high. The study concludes that the adaptive ability of students in responding to pressure is relatively good, although the commitment dimension still requires strengthening to maintain motivation and engagement during pesantren activities.